2014
DOI: 10.1111/1440-1681.12281
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs differentially regulated in cardiac and skeletal muscle in health and disease: Potential drug targets?

Abstract: The identification of non-coding RNA species, previously thought of as 'junk' DNA, adds a new dimension of complexity to the regulation of DNA, RNA and protein. MicroRNAs are short non-coding RNA species that control gene expression, are dysregulated in settings of cardiac and skeletal muscle disease and have emerged as promising therapeutic targets. MicroRNAs specifically enriched in cardiac and skeletal muscle are called myomiRs and play an important role in cardiac pathology and skeletal muscle biology. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 119 publications
1
23
0
2
Order By: Relevance
“…MicroRNAs (miRNAs) are small, non-protein-coding RNA (usually 22 nucleotides) molecules, which function in RNA silencing and post-transcriptional regulation of target gene expression (Rupaimoole and Slack, 2017). Accumulating evidence has shown that miRNAs are involved in nearly all cancer types, acting as tumor oncogenes or suppressors and taking part in cell proliferation, differentiation, and metastasis (Winbanks et al, 2014;Vorvis et al, 2016). It is well-established that a large number of specific miRNAs are involved in the carcinogenesis and development of tumors by regulating the expressions of their targeted mRNAs (Inui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, non-protein-coding RNA (usually 22 nucleotides) molecules, which function in RNA silencing and post-transcriptional regulation of target gene expression (Rupaimoole and Slack, 2017). Accumulating evidence has shown that miRNAs are involved in nearly all cancer types, acting as tumor oncogenes or suppressors and taking part in cell proliferation, differentiation, and metastasis (Winbanks et al, 2014;Vorvis et al, 2016). It is well-established that a large number of specific miRNAs are involved in the carcinogenesis and development of tumors by regulating the expressions of their targeted mRNAs (Inui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miR-208, a member of the miR-208 family, is differentially expressed during heart developmental and plays an essential role in normal cardiac conduction [34, 35]. Both over-expression and under-expression of miR-208a has been associated with cardiac arrhythmia [36], with apoptosis in ischemic cardiomyocytes [37] and generally with heart diseases [38]. Down-regulation of miR-208a in atrial myocardial tissues of patients with CHD after CPB underscore the integral function of this miRNA in regulating cell morphology and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-222 has a documented function in regulating cell proliferation and is involved in the vascular smooth muscle cells differentiation [38, 44]. In neonatal cardiomyocytes, miR-222 induces cellular hypertrophy and proliferation and inhibits apoptosis after ischemic injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…Increased synthesis and secretion of growth hormone (GH) and insulin growth factor 1 (IGF-1) during physical exercise results in activation of the PI-3K/Akt and SRE/SRF signaling pathways, leading to an increase in mitochondrial density, expression of contractile proteins, and hypertrophy of skeletal muscle. Decrease release of myostatin by physical exercise, mainly strength exercises, by the other hand, attenuates the inhibition of myogenesis in satellite cells, resulting in skeletal muscle mass increase [91].…”
Section: Physical Exercise and Gene Expressionmentioning
confidence: 99%